The Relationship between Dialysis Adequacy and Fatigue in Patients on Maintenance Hemodialysis - Sri Suparti; Sodikin Sodikin; Endiyono Endiyono (Jurnal Keperawatan Padjadjaran, 2020)
Fatigue and inadequacy dialysis are common problem in hemodialysis patients. The dialysis inadequacy can cause an increased progression of impaired renal function, as well as the increased morbidity and mortality, and declining productivity of hemodialysis patients. Fatigue prevalence ranged from 44,7–97% from mild to severe. Fatigue is a common complaint of hemodialysis patients that can lower physical function and life quality. To determine the correlation between adequacy and the fatigue level of the patients with End Stage Renal Disease (ESRD) undergoing hemodialysis. This study used a descriptive analytic and cross sectional approach involving 75 respondents and the FACIT-G Questionnaire was used to collect the data. The inclusion criteria are male and female patients aged 18–70, undergoing hemodialysis for more than 3 months with a frequency of 2 times at least 4 hours, composmentis patients. The adequacy hemodialysis was assessed using the Kt/V formula. All data were collected during the session of hemodialysis. Pearson Product moment test wes used to analyze the data. The mean dialysis adequacy was 1.43±0.380, 57(76%) only 13 (17.3%) patients had adequate dialysis (minimum laboratory standard Kt / v = 1.8) and inadequate were 62 (82.7%) patients. The mean of fatigue was 20.07 and 62 (82.7%) respondents experienced severe fatigue. There was no significant correlation between adequacy and the fatigue level of the patients with ESRD undergoing hemodialysis with p value 0.504 (α> 0.05). Mostly patients had inadequate dialysis, both adequate and inadequate dialysis patients had experience fatigue from mild to severe. Multiple individuale and personnel factors affect dialysis adequacy directly or conversely.